SCALE IS SYNONYMOUS OF FAT? MUSCULAÇÃO DIMINISHES OR NOT IT FAT? A LITERATURE REVISION (Fiep Bulletin - online, 2014)
The study it is based on literature revision, with objective to try to clarify the possible increases of weight, mensurados in the scale for individuals that practise musculação. The presented topics had been: analysis of the fabric adiposo, methods for the evaluation of the corporal composition and training of force. The objective of this article and to demonstrate that the increase of weight surveyed in the scale in individuals that practise musculação, in some cases it must to the increase of the lean mass and not of the fat mass.
Keywords: Corporal composition; Anthropometry; force training